2015
DOI: 10.1016/j.amjcard.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Combined Non–High-Density Lipoprotein Cholesterol and Apolipoprotein B With Atherosclerosis in Adults With Type 1 Diabetes Mellitus

Abstract: Apolipoprotein B (apoB) and nonHDL-cholesterol (nonHDL-C) are cardiovascular disease (CVD) risk markers, although data in adults with type 1 diabetes mellitus (DM) are limited. We hypothesized that elevated apoB and nonHDL-C would be associated with greater odds of coronary artery calcification progression (CACp), a measure of coronary atherosclerosis, than either category alone in adults with type 1 DM. We grouped subjects with type 1 DM (n=652) into four groups; elevated apoB (≥90mg/dL) and elevated nonHDL-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Several studies have tried to better characterize CVD risk in patients with T1DM [ 32 , 33 ]. One of them showed that combining non-HDL cholesterol and apolipoprotein B provides a better estimation of increased CVD risk in adults with T1DM than any of these values used alone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tried to better characterize CVD risk in patients with T1DM [ 32 , 33 ]. One of them showed that combining non-HDL cholesterol and apolipoprotein B provides a better estimation of increased CVD risk in adults with T1DM than any of these values used alone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-HDL cholesterol is regarded as an important indicator of cardiovascular risk [40]. In addition, soy leaves have been reported to reduce non-HDL cholesterol, although serum total cholesterol showed a trend of lowering effects in hamsters [26].…”
Section: Discussionmentioning
confidence: 99%
“…CTCA can also be used to generate CAC scores. Patients with T1DM with both elevated apoB and non-HDL cholesterol have greater CAC [ 82 ]. Progression of CAC is also strongly associated with HbA1c and glycaemic variability [ 83 ].…”
Section: Surrogate Measurements Of Atherosclerosis: Screening and Detmentioning
confidence: 99%